Comparison of trans-abdominal preperitoneal repair with Lichtenstein tension-free hernioplasty: A prospective study - Tanweer Karim; Vivek Kumar Katiyar; Atul Jain; Gaurav Patel; Sajid Maqbul Nurbhai; Ram Bharosh Kumar (Formosan Journal of Surgery, 2021)
Background: The concept of hernial repair underwent evolution from Bassini's repair to Lichtenstein tension-free repair with the introduction of polyethylene mesh. Recently, some of the prosthetic biomaterials have been combined to form composite mesh to minimize undesirable side effects. Mesh placement can be achieved by both open and laparoscopic techniques. Although many studies have explored the relative merits and potential risks of laparoscopic surgery for the repair of inguinal hernia, most individual trials have been too small to show clear benefits of one type of surgical repair over another. Materials and Methods: A randomized comparative study, was conducted for duration of 18 months. Patients of Unilateral Uncomplicated Inguinal hernia between the age group of 18-60 years, was randomized between two groups. Patient were operated by Surgeons having requisite experience of TAPP repair and Lichtenstein repair. Results: A total of 110 patients included in this study were male with unilateral uncomplicated inguinal hernia. The mean operative time for open Lichtenstein mesh repair and TAPP was 52.85 min and 64.27 min, respectively. The postoperative pain score (as per visual analog scoring) was statistically significantly less in laparoscopic TAPP group as compared to that of open Lichtenstein group (P < 0.05). No major complications were noted in either Lichtenstein group or TAPP group. The minor complication rate was 20.0% for open Lichtenstein group and 7.27% for laparoscopic TAPP group. The mean time to return to work was earlier for TAPP group (12.97 days) as compared to that of Lichtenstein group (17.84 days). Conclusion: The results support the view that laparoscopic TAPP mesh repair is as safe and efficient as Lichtenstein inguinal hernia repair and should be an available option for all patients requiring elective hernioplasty.